Environment and farm factors associated with exposure to Theileria parva infection in cattle under traditional mixed farming system in Mbeere District, Kenya - Gachohi, John M.; Kitala, P.M.; Ngumi, P.N.; Skilton, Robert A. (Springer, 2011)
The objective of this study was to investigate the relationship between seroprevalence to Theileria parva infection in cattle and potential environmental and farm-level effects in 80 farms under traditional crop–livestock system in Mbeere District, Kenya. A standardized questionnaire was used to collect the effects characteristics as related to T. parva infection epidemiology. Serum samples were collected from 440 cattle of all ages for detection of T. parva antibodies by the enzyme-linked immunosorbent assay technique. The association between the variables was assessed using a generalized estimation equation logistic regression model. The overall T. parva seroprevalence, accounting for correlation of responses, was 19.3% (95% confidence interval (CI) 14%, 25%). Two variables, “administrative division” and “presence of the vector tick on the farm”, were significantly associated with the T. parva seroresponse. Respectively, cattle from farms in Gachoka, Evurore, and Mwea divisions were (and their 95% CI) 1.3 (0.36, 4.8), 4.4 (1.2, 15.9), and 15.2 (4.9, 47.1) times more likely to be seropositive relative to those from Siakago Division (P=0.000). Cattle from farms in which the vector tick was present were 2.9 (1.2, 6.7) times more likely to be seropositive (P=0.011). Results of this study suggested that both environmental and farm factors may be associated with T. parva infection epidemiology in Mbeere District. Under such circumstances, characterization of environmental suitability for the vector tick and corresponding environment-specific farm management practices in the district is required both for improved understanding of the disease and in planning disease control programs.